SHEIKH YŪSUF AL-MAQASSARY AND HIS REFORM IDEAS IN THE SPREAD OF ISLAM IN GOWA-MAKASSAR IN THE SEVENTEENTH CENTURY - Abdul Rasyid Masri (Fakultas Dakwah dan Komunikasi, 2019)
This paper relates to the brief history of Sheikh Yῡsuf al-Makassary as well as his brief role in the Spread of Islam in Gowa-Makassar as his birth land.Sheikh Yῡsuf was born in 1626 M and grew up among noble families of Gowa-Tallo Kingdoms and then travelled to seek and deepen his Islamic knowledge from Aceh, India to the middle East (1645-1668) or for around 23 years and then he became a great ṣῡfῑ and left many of his treatises for Islamic community, especially for his followers, which are most of them still preserved at Universiteit Bibliotheq Leiden and the national museum of Jakarta at the present day. The main concept of Islamic mysticism of Sheikh Yῡsuf as one of his reform in the spread of Islam in Gowa-Makassar is the purification of belief (‘aqῑdah) in the Oneness of Allāh or in the Unity of God (tawḥῑd). This is his attempt to explain God’s transcendence (Ilāh) on His creatures. In a quoted al-Ikhlash verse (QS. 112:1-4) and al-Shura’ verse of al-Qur’an that there is nothing comparable to Him (QS. 42: 11), Sheikh Yῡsuf emphasized that the Oneness of Allāh is infinite and absolute. Tawḥῑd is the essential component in Islam. Moreover he compares “the immaculate tawḥῑd with a leafy tree; Gnostic knowledge (ma‘rῑfa) is its branches and leaves, and devotional services (‘ibādah) are its fruit.” Further he said that if you got the tree, you will get its branches and leaves, and if you got them, you will even look for fruit of the tree. If you did not get its branches and leaves, it is impossible to get its fruit. Therefore, tawḥῑd without ma‘rῑfah is like a tree without branches and leaves, and it is impossible to get its fruit, except if the branches and leaves of the tree grew up again, then its fruit can be hoped. In other words, only a man, who has tawḥῑd with ma‘rῑfa, could perform devotional service well to God. This teaching was used as the basic reform ideas in the spread of Islam in Gowa-Macassar, South Sulawesi and then brought a big changing to the cultural of his society and then made Muslim in Gowa-Makassar to be a more fervent Muslim. Therefore, one of the reform movements in his homeland was that he tried to pull out and then to release the people of Gowa-Makassar from the bad habits such as activities in serving idols / idols places, alcoholic beverages, cockfighting and gambling in crowded places. Because those can be a great danger to his native land; he said that the collapse of an empire because of the weakness of the faith of its people. On the other hand, the strength of an empire can guarantee the enforcement of sharῑ‘ah h. But it also depends on the leader. A good leader / ruler is one who able to enforce the Islamic law or sharῑ‘ah h in the middle of his society. Thus the main priority in the renewal of his mystical teachings for Muslims believers especially in Gowa Makassar, South Sulawesi, Indonesia is the purification of confidence by implementing ṣῡfism which is more oriented to the sharῑ‘ah , where he tried hard to reconcile sharῑ‘ah and ḥaqῑqah. Among the various types of ṣῡfῑ orders affiliated with him, Ṭarῑqat al-Khalwatiyya is the famous one, which is later more popular with Khalwatiyyat al-Yῡsufiyya that has found fertile land especially in South Sulawesi.